Pharmacist Profession Introduction for Children and First Aid Education for Teachers of Al Biruni Cerdas Mulia Kindergarten Tasikmalaya - Hanifa, Hanina Liddini; Fadhilla, Genialita; Fatimah, Sitti (Fakultas Kewirausahaan Universitas Garut, 2024)
The introduction of the pharmacist profession serves as an effort to broaden children's understanding of the roles and contributions of health professions in daily life, including the proper use of medications. Additionally, teachers in kindergartens play a central role in ensuring safety at school, including performing first aid when necessary. Therefore, this community service program aims to enhance the knowledge of Al Biruni Kindergarten students about the pharmacist profession and to improve the knowledge of Al Biruni Kindergarten teachers on first aid measures to prevent fatal accidents. The methods used included introducing the pharmacist profession through an audiovisual presentation and simple pharmaceutical job simulations conducted by the children, as well as providing first aid seminar to teachers and evaluating their knowledge before and after the session. Questionnaire result showed an increase in teachers' knowledge from 78.12% to 93.75% in the